Przekład zakorzeniony jako przejaw manipulizmu na podstawie odbioru "Kubusia Puchatka" i "Fredzi Phi-Phi" - Jolanta Staniuk (Ksiegarnia Akademicka Publishing, 2019)
Rooted Translation as an Example of Manipulation on the Basis of the Reception of Kubuś Puchatek and Fredzia Phi-Phi The new rendition of a text whose previous translation has already entered the literary canon of a given language can be a challenge. The existence of a rooted translation in one literary system can constitute an obstacle for the future translators of a given text. The influence of such a commonly accepted translation, ingrained in the minds of readers, can be seen as an example of manipulation. The examination of the two Polish renditions of the same book – Winnie-the-Pooh by A.A. Milne can further prove this point. While the first translation, done by Irena Tuwim, was considered a great success and entered the Polish literary canon, the next translator – Monika Adamczyk had to deal with numerous criticisms and the readers’ rejection because her version of the book was significantly different from her predecessor’s.